Efectos biológicos de las nanopartículas de óxido de hierro superparamagnéticas empleadas en el diagnóstico de enfermedades neuroinflamatorias (2021)
Neuroinflammation is a pathophysiological feature of brain disorders, including neurodegenerative diseases, whose timely diagnosis constitutes a biomedical challenge. The development of new diagnostic technologies includes the use of superparamagnetic iron oxide nanoparticles, which offer ferromagnetic characteristics that allow them to be used as contrast agents in magnetic resonance imaging. Additionally, by conjugating these nanoparticles with specific markers, the confidence level of the clinical diagnosis increases. Therefore, it is necessary to understand the biological effects of these nanoparticles in order to be scaled to clinical practice. The main effects of superparamagnetic iron oxide nanoparticles in vitro have been reported to include: decreased cell viability, oxygen free radical formation, DNA damage, and protein misfolding. At the in vivo level, accumulation in the liver, lungs and kidneys has been identified, favoring the production of reactive oxygen species. Therefore, it is essential to consider the coating, dose, particle size and the physiological system to be applied. This review identifies the effects of superparamagnetic iron oxide nanoparticles at the cellular and tissue level, to be used in the diagnostic area of neuroinflammatory diseases.